2004
DOI: 10.1016/s0002-9440(10)63753-4
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Proprotein Convertases Enhances Cell Migration and Metastases Development of Human Colon Carcinoma Cells in a Rat Model

Abstract: Although proprotein convertases are involved in tumor development, nothing is known about their role in metastatic dissemination. To investigate the involvement of convertase inhibition, we used human colon carcinoma cells overexpressing ␣1-antitrypsin Portland (␣1-PDX, PDX39P cells), a potent convertase inhibitor. We previously reported that these cells bear uncleaved integrin ␣ subunits and display an altered attachment to vitronectin that is correlated with defects in the intracellular signaling pathways ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
13
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 48 publications
1
13
0
Order By: Relevance
“…Earlier reports showed that a1-PDX overexpression in different tumor cell systems resulted in a reduced invasiveness and in vivo tumorigenicity in nude mice (2,8,16). In other studies, this inhibitor was found to increase cell migration and accelerate the process of metastasis (17). Accordingly, overexpression of Furin has been established in various types of cancers (2,10,14) and has been linked to aggressive behavior in some model systems (14).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Earlier reports showed that a1-PDX overexpression in different tumor cell systems resulted in a reduced invasiveness and in vivo tumorigenicity in nude mice (2,8,16). In other studies, this inhibitor was found to increase cell migration and accelerate the process of metastasis (17). Accordingly, overexpression of Furin has been established in various types of cancers (2,10,14) and has been linked to aggressive behavior in some model systems (14).…”
Section: Discussionmentioning
confidence: 96%
“…Student's t test was used for statistical analysis. *, P < 0.05; **, P < 0.01; ***, P < 0.001. expressed in various cancers (10,(14)(15)(16)(17). Earlier reports showed that a1-PDX overexpression in different tumor cell systems resulted in a reduced invasiveness and in vivo tumorigenicity in nude mice (2,8,16).…”
Section: Discussionmentioning
confidence: 99%
“…However, the α5 and αv subunits belong to a second subset of α integrin subunits lacking the I domain. They instead undergo an endoproteolytic cleavage that is essential for integrin function Nejjari et al, 2004). Ligation of α5β1 and αvβ3 integrins also leads to conformational changes that are propagated all along the molecule (Takagi et al, 2001;Takagi et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…This same mechanism would possibly be shared by all other types of cancers, including CRC. It is known that both normal and cancer intestinal cells secrete AAT to neutralize elastase [22], which is present in high concentrations in CRC cells, in an attempt to maintain the proteaseantiprotease balance, preventing the activation of procathepsin B and proprotein convertase, and reducing production of Tumor Necrosis Factor (TNF) alpha, and Interleukin-1a, which in turn prevents liver metastases [23][24][25]. There is also some evidence of a relationship between AAT deficiency and the development of neoplasms of the urinary bladder, gallbladder, and malignant lymphomas [12][13][14].…”
Section: Discussionmentioning
confidence: 99%